Evaluating the effectiveness of Doppler frequency shift determination using pilots in broadband transmission - Agnieszka Czapiewska; Andrzej Łuksza; Ryszard Studański; Łukasz Wojewódka; Andrzej Żak (International Journal of Electronics and Telecommunications)
In underwater communications, reciprocal motion between transmitter and receiver has a significant impact on reception quality. In orthogonal broadband systems that provide high bit rates, this problem becomes more important, especially in the higher frequency range, where the absolute Doppler shift is the greatest. Due to the low propagation speed of acoustic wave underwater, a substantial difference exists between the Doppler shift for lower and upper frequencies of the utilized spectrum. Consequently, a frequency-independent Doppler shift factor is employed. One of the most popular methods for determining the Doppler shift is the use of pilots. The problem of selecting the number and determining the frequency of pilots in such a way as to obtain the lowest possible error rate was identified. Real-world testing was conducted in a multipath propagation environment with relative speeds of up to 1.5 m/s. The effectiveness of Doppler shift determination was evaluated by analyzing the bit error rate. The results of the conducted tests indicate that, based on the achieved error rate, it is sufficient to employ 7 pilots positioned at low frequencies.